2019
DOI: 10.2147/oarrr.s167990
|View full text |Cite
|
Sign up to set email alerts
|

<p>Managing fatigue in patients with primary Sj&ouml;gren&rsquo;s syndrome: challenges and solutions</p>

Abstract: Primary Sjögren’s syndrome (pSS) patients identify fatigue as their most important symptom and the one most difficult to cope with, but there are still many challenges and few solutions to manage this debilitating symptom. Promising pharmacological treatments, such as rituximab, have failed in more stringent tests including randomized controlled trials (RCTs) and meta-analysis. While non-pharmacological interventions may be safer, less costly, and address other common comorbidities, to date only aerobic exerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 93 publications
1
13
0
Order By: Relevance
“…However, a multidimensional assessment may provide a more complete picture, improving understanding of the clinical associations of fatigue and potential treatment. Studies on pSS have also used many non-disease specific multi-item questionnaires (15,16) which would be most recommended when one of the study objectives is to compare fatigue across diseases. Commonly used instruments are summarized in Table 1.…”
Section: Instruments For Measuring Fatigue In Pssmentioning
confidence: 99%
“…However, a multidimensional assessment may provide a more complete picture, improving understanding of the clinical associations of fatigue and potential treatment. Studies on pSS have also used many non-disease specific multi-item questionnaires (15,16) which would be most recommended when one of the study objectives is to compare fatigue across diseases. Commonly used instruments are summarized in Table 1.…”
Section: Instruments For Measuring Fatigue In Pssmentioning
confidence: 99%
“…The cause of fatigue in pSS patients is still unknown, and current interventions for managing fatigue are insufficient. [ 35 ] Our study and others [ 14 ] have identified associations between fatigue and sleep quality, suggesting that sleep management may be necessary for treating symptoms of fatigue. Cognitive behavioral therapy for insomnia improves sleep, fatigue, and QOL in patients with fibromyalgia, [ 36 ] suggesting that it could be effective in treating these symptoms in patients with pSS.…”
Section: Discussionmentioning
confidence: 83%
“…13 Different types of questionnaires including the multidimensional fatigue inventory, fatigue impact scale, fatigue severity scale (FSS), and visual analogue fatigue scale to be analyzed for the assessment of symptoms. 12,14 For the measure of fatigue severity in patients with systemic lupus erythematosus (SLE), and multiple sclerosis (MS), the FSS was initially developed by Krupp and his co-workers in the years of 1989, the FSS is a simple and easy to use self-reported questionnaire. It consists of nine statements that assess the seriousness of the patient's symptoms of exhaustion in terms of how these symptoms influence activities of daily living, physical function, exercise, and motivation around the day over the past week.…”
Section: Introductionmentioning
confidence: 99%
“… 11 A number of variable clinical studies have been used different existing methods and questionnaires to measure fatigue in systemic rheumatic diseases including pSS patients; however, not all of these tools are specific for pSS and it is not clear that the fatigue measurement methods will be able to understand the nature and improvement of fatigue inpatient with pSS in response to medical intervention. 12 Fatigue has been included as one of the components of the European League Against Rheumatism (EULAR) Sjogren’s syndrome patient reported index (ESSPRI) evaluated by a visual analogue scale (VAS) from 0 to 10. 13 Different types of questionnaires including the multidimensional fatigue inventory, fatigue impact scale, fatigue severity scale (FSS), and visual analogue fatigue scale to be analyzed for the assessment of symptoms.…”
Section: Introductionmentioning
confidence: 99%